?INFLUENCE OF TWO SEWAGE SLUDGE SOURCE ON PLANT GROWTH AND NUTRIENTS UPTAKE - ELEIWA, M.E.; RABIE, M.H.; NEGM, A.Y.; ABDEL, M.P. (Biological Sciences - PJSIR, 1996)
The effect of dried sewage sludge from two sources (Suez and Giza governorates) on faba bean growing on sandy soil followed by sorghum to test the residual effect of the sludge on it's growth and mineral content was studied in a pot experiment. The results showed that, for faba bean, the number of nodules/plant, plant height and leaf area increased significantly due to application of either Suez or Giza sludge up to 5%. The former sludge increased the yield not up to 5% while the latter gave only 2.5% increase. Data also revealed that shoot and root dry weights of sorghum plants signiticantly increased by Suez and Giza sludge by 7.5 and 5% respectively. The higher rate (10%) of Giza sludge inhibited root growth. Nitrogen and P contents increased by either sludge application. Zn and Cu con- tents of roots and shoots increased by increasing the rate of Suez sludge, while Fe, Mn, Ni and Cr contents of roots were slightly affected and they remained unchanged in the shoots. Giza sludge applications caused progressive increase in most of heavy metals in sorghum plants specially Cr, According to the Zn equivalent, the maximum rate of dried sludge to be added to the soil is 78.13 tons/fed for Giza sludge and 160.25 tons/fed for Suez sludge before the safe limits are exceeded. The addition may be divided over long period.